Ze’enah u-Re’enah: a critical translation into English - Faierstein, Morris M. (Studia Judaica, 2017)
This book is the first scholarly English translation of the Ze’enah U-Re’enah, a Jewish classic originally published in the beginning of the seventeenth century, and was the first significant anthological commentary on the Torah, Haftorot and five Megillot. The Ze’enah U-Re’enah is a major text that was talked about but has not adequately studied, although it has been published in two hundred and seventy-four editions, including the Yiddish text and partial translation into several languages. Many generations of Jewish men and women have studied the Torah through the Rabbinic and medieval commentaries that the author of the Ze’enah U-Re’enah collected and translated in his work. It shaped their understanding of Jewish traditions and the lives of Biblical heroes and heroines. The Ze’enah U-Re’enah can teach us much about the influence of biblical commentaries, popular Jewish theology, folkways, and religious practices. This translation is based on the earliest editions of the Ze’enah U-Re’enah, and the notes annotate the primary sources utilized by the author.